Question not found

Not a good answer? Get an answer now. (Free)

Rating

There are no new answers.

Score:
Find the product.
(2p + 7)(3p - 9)
6p2- 3p- 63
6p2+ 3p- 63
6p2+ 39p- 63
6p2+ 3p- 2 **Weegy:** Answer = 12 = (2.5/-5) x -6 = -2 x -6 =12 (More)

Question

Expert Answered

Updated 5/1/2012 6:23:13 AM

2 Answers/Comments

(2p + 7)(3p - 9) = 6p^2 + 3p - 63

Added 5/1/2012 6:23:13 AM

This answer has been added to the Weegy Knowledgebase

Find the product.
(6a + b)2
a.12a2+ ab + b2
b.36a2+ ab + 36b2
c.36a2+ 12ab + b2
d.36a2+ b2

Question

Not Answered

Updated 4/10/2012 3:55:29 PM

1 Answer/Comment

(6a + b)^2

= (6a + b)(6a + b)

= 36a^2 + 12ab + b^2

= (6a + b)(6a + b)

= 36a^2 + 12ab + b^2

Added 4/10/2012 3:55:29 PM

This answer has been added to the Weegy Knowledgebase

Simplify 5 + 2{x - 4[3x + 7(2 - x)]}.
(a)34x - 107
(b)34x - 107
(c)34x + 107

Question

Not Answered

Updated 4/10/2012 4:04:41 PM

1 Answer/Comment

5 + 2{x - 4[3x + 7(2 - x)]}

=5 + 2{x -4[3x + 14 - 7x]}

=5 + 2{x - 12x - 56 + 28x}

=5 + 2x - 24x - 112 + 56x

=34x - 107

=5 + 2{x -4[3x + 14 - 7x]}

=5 + 2{x - 12x - 56 + 28x}

=5 + 2x - 24x - 112 + 56x

=34x - 107

Added 4/10/2012 4:04:42 PM

This answer has been added to the Weegy Knowledgebase

Find the product. (6a + b)2 a.12a2+ ab + b2 b.36a2+ ab + 36b2 c.36a2+ 12ab + b2 d.36a2+ b2

Question

Not Answered

Updated 5/5/2014 3:54:41 PM

1 Answer/Comment

(6a + b)^2;

(6a + b)(6a + b);

36a^2 + 6ab + 6ab + b^2

= 36a^2 + 12ab + b^2

(6a + b)(6a + b);

36a^2 + 6ab + 6ab + b^2

= 36a^2 + 12ab + b^2

Added 5/5/2014 3:54:41 PM

This answer has been confirmed as correct, not copied, and helpful.

Find the product. (6a + b)2 a.12a2+ ab + b2 b.36a2+ ab + 36b2 c.36a2+ 12ab + b2 d.36a2+ b2

Question

Not Answered

Updated 2/15/2015 7:44:04 PM

1 Answer/Comment

27,384,235 questions answered

There are no comments.